Radiological and Surgical Assessment of Proximity of Roots of Mandibular Third Molar to the Inferior Alveolar Canal in Impacted Teeth - Tushar K. Bandiwadekar; David P. Tauro; Sachin K. Malagi; Abhinav Dubey; Kolla Advait; Sumit Bhatt (Journal of Pharmacy and Bioallied Sciences, 2024)
Background and Objective: A mandibular canal around the lower third molar roots house the inferior alveolar nerve (IAN). There is a risk of nerve injury during surgical tooth extraction. Methods: The College of Dental Sciences at Davangere’s Department of Oral and Maxillofacial Surgery served as the outpatient setting for this investigation. The study comprised one hundred participants who were going to have their mandibular third molars surgically extracted. The risk of IAN injury was evaluated by comparing the radiographic findings from preoperative orthopantomography and intraoral periapical radiographs with intraoperative observations. Results: The study revealed that the patient’s age did not have a significant correlation with the risk of nerve injury. However, cases involving bony impactions were found to have a higher risk of IAN damage. Additionally, mesioangular impactions and radiographic indicators, such as root deflection, were associated with an elevated risk of nerve injury. Conclusion: To reduce the risk of IAN injury during the extraction of mandibular third molars, it is essential to have a detailed understanding of the relevant anatomical features and to plan the surgical procedure meticulously.